Abdominal wall repair using cross linked bovine diaphragm with ultrasound therapy in rabbits - SHARMA, A K; BABU, KAILASH; KUMAR, NAVEEN; MAITI, S K; GOSWAMI, T K; SHARMA, ANIL K (The Indian Journal of Animal Sciences, 2011)
Healthy rabbits (20) of both sex were divided into 3 groups to evaluate ultrasound therapy in hemioplasty. First and second groups comprised 8 animals each and group 3 had 4 animals (control). In group 1 and 2 the experinlental abdominal wall defects were repaired with glutaraldehyde treated bovine diaphragm and in group 3 the autografting was perfonned. In group 2, additionally, pulse ultrasound therapy at the reconstructed site was given @ 0.5 wattlcln2 for 5 min on alternate day from day 3 postoperative for 2 weeks. Surgery was perfonned under xylazine-ketamine anaesthesia. There was significant rise in temperature and differential leucocyte count for 3 days and 7 days, respectively, in each group. Nonsignificant increase in antibody titre was recorded at 90 days but graft rejection was not observed. The inflammatory reaction started to reduce after 3 days in each group, thereafter, the reduction in tissue reaction was slightly quicker in group 2 and the complete healing occurred at 60 days in these animals. The increase in collagen and hydroxyproline at 21 days and decrease in hexosamine at 60 and 90 days was significant. The elastin increased with the progression of healing. The changes in histochemical parameters were almost identical in all the animals of different groups. Â